Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please could someone advise if I have interpreted this problem correctly

Let $X$ have an exponential distribution with a mean of $i = 20$

(1) Compute $P(X>40 \;| \;X>10)$

I believe the correct solution here is to find $P(X>40)$ because of the inclusion / exclusion principle. That is if we define the event $A = P(X>40)$ and the event $B = P(X>10)$. In addition, define $A \cap B$ as $P(X>10)$. Then to compute (1) we find the following $P(X>40) \cup P(X>10) - P(X>10)$ which is

$$1- (1-e^{-\frac{30}{20}})=0.2231$$

EDIT Due to the "memorylessness" of the probability distribution

$$P(X>40 \mid X>10)= P(X>30) $$

Thanks in advance

share|improve this question
4  
First, I think you meant to define $A=\{X>40\}$ and $B=\{X>10\}$. Then you can't define $A\cap B$, because it is already decided by $A$ and $B$. In particular $ A\cap B=A$, because $B\subseteq A$. Second, unions are to be put between sets and not numbers, i.e. $P(X>40)\cup P(X>10)$ does not make sense. Third, note that the exponential distribution has the memorylessness property. –  Stefan Hansen Jan 11 '13 at 12:46
    
+1 Stefan ..Thanks for the heads up about memorylessness –  bosra Jan 11 '13 at 12:52
1  
Are you having trouble calculating $P(X>30)$? –  Stefan Hansen Jan 11 '13 at 12:55
    
If you do, look at the cumulative distribution function of the exponential function. –  fabee Jan 11 '13 at 13:09
1  
It is correct. $ $ –  Did Jan 14 '13 at 11:02

1 Answer 1

Yes, due to "memorylessness" of an exponential distribution, if $s>0$, $t>0$, then $$P(X>s+t\mid X>s) = P(X>t) = e^{-\lambda t}.$$

We can find that if we simply calculate the expression, the result will show the "memorylessness":

$$ \begin{align} P(X>s+t\mid X>s) &= \frac{P\big(X>s+t\cap X>s\big)}{P(X>s)} = \frac{P(X>s+t)}{P(X>s)} \\ &= \frac{\int_{s+t}^{\infty}\lambda e^{-\lambda x}dx}{\int_{s}^{\infty}\lambda e^{-\lambda x}dx} = e^{-\lambda t} = P(X>t),\quad (s>0,t>0). \end{align} $$

share|improve this answer
1  
$\cap$ is used between sets, not numbers and hence $P(X>s+t)\cap P(X>s)$ does not make sense. The correct notation is $P(\{X>s+t\}\cap\{X>s\})$ or in short-hand notation $P(X>s+t,X>s)$. –  Stefan Hansen Apr 30 '13 at 12:46
    
Yes, that is right. Thank you for the correction. –  Tianyu Zheng May 1 '13 at 1:32

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.